Improving Mathematics Critical Thinking Ability and Self Regulated Learning Of High School Method Through IMPROVE Students - Dinar Andriyani; Citra Megiana Pertiwi (IKIP Siliwangi, 2020)
The low critical thinking skills and self-regulated learning in the field are the backgrounds for this research. This study aims to examine the improvement of mathematical critical thinking skills and self- regulated learning using the IMPROVE method and by using ordinary learning. The research method used was an experimental method with a pretest-posttest group research design involving two groups and randomized class sampling. The population is all high school students in Purwakarta Regency. All high schools in Purwakarta were randomly selected, SMAN 1 Maniis was selected, the sample was randomly selected by two classes, class XI Mia 2 as the control class and class XI Mia 1 as the experimental class. Data collection in this study was in the form of tests and non-tests, then the data on the scores of students' mathematical critical thinking skills and learning independence were analyzed using descriptive and inferential statistics using the two-difference test means. Based on the results of the study, both from the results of data analysis and hypothesis testing, the authors conclude that the achievement and improvement of mathematical critical thinking skills and self- regulated learning students whose learning using the IMPROVE method are better than those using ordinary learning.